Soloway's Rainfall Problem Has Become Harder - Simon (2013 Learning and Teaching in Computing and Engineering (LaTiCE), 2013)
Discussing the use of plans in programming and in programming education, Soloway describes a programming task that has come to be known as the rainfall problem. This problem was used in a number of empirical experiments in the 1980s and 1990s, and was generally recognised as being quite difficult for student programmers. This paper reports that when the rainfall problem was recently used as an examination question in an introductory programming course, the students performed extremely poorly on it. These students are presumably no better than the many students who have been set this problem in the past, but it also appears that the problem has become harder than it was 20 years ago. For example, the problem assumes that loop-controlled keyboard input is standard, whereas in many programming environments nowadays the standard has become event-driven GUI input. As a consequence of this change, students are less likely to be familiar with loop-controlled keyboard input and with the use of a sentinel to terminate input, another feature of the rainfall problem. While there is potential value in comparing the performance of today's students with that in the literature of past decades, it is important to consider changes in technology that might impose a different level of challenge on the same problem.